Optimization of CO2 Concentration on Mortality of Various Stages of Callosobruchus maculatus and Development of Controlled Atmosphere Storage Structure for Black Gram Grains. (20th July 2022) - Shankar, V. Siva; Velmurugan, G.; Kaliappan, S.; Baskara Sethupathy, S.; Sekar, S.; Patil, Pravin P.; Anitha, G.; Kailo, Geremew Geidare
Abstract : Pulse beetle ( Callosobruchus maculatus ) is a common weevil that is responsible for up to 24% of stored pulse losses. Using black gram grain storage, the efficiency of carbon dioxide gas against all life stages of Callosobruchus maculatus insects was tested at various concentrations and exposure times. The trials were carried out in pilot bins with a capacity of 25 kg. At a CO2 concentration of 50%, complete mortality of the egg stage of Callosobruchus maculatus was attained after 72 h of continuous exposure. At a CO2 concentration of 60% for 48 h, 100% larva mortality was achieved. At the most tolerant stage of pupa, recorded complete mortality is at a CO2 concentration of 70% for 96 hours of the exposure period. Adult insects are especially vulnerable to the high CO2 concentration. Adult mortality was achieved at a concentration of 20% with an exposure period of 48 h. The CO2 -treated black grams were then stored for three months with the optimized CO2 concentration and exposure period, while physiochemical parameters such as water retention capacity and physiological loss in weight were determined. Grain stored in the silo showing significant 100% mortality of egg was measured after 20-25 days of observation. The use of a controlled atmosphere storage bin increased the mortality of the insect C. maculatus at all developmental stages, by means of increasing CO2 concentration and exposure time. Grain stored in a controlled atmosphere silo showed minimum losses of grain (4.10%) compared to the gunny bag storage (22.56%).